2011
DOI: 10.1093/infdis/jir011
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death 1 and Cytokine Inducible SH2-Containing Protein Dependent Expansion of Regulatory T Cells Upon Stimulation With Mycobacterium tuberculosis

Abstract: We previously found that CD4(+)CD25(+)FoxP3(+) regulatory T cells (Tregs) expand in response to Mycobacterium tuberculosis infection in individuals who are healthy tuberculin reactors, but not in tuberculin-negative individuals. We also found that the M. tuberculosis mannose-capped lipoarabinomannan and prostaglandin E2 produced by monocytes are involved in Treg expansion. In this study, we found that Tregs expanded from CD4(+)CCR4(+) cells but not from CCR4(-) cells. However, introduction of CCR4 small interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…T reg cells also upregulate PD-1 expression on their surfaces during chronic viral infection (20). PD-1:PD-L1 interaction has a critical role in promoting the conversion of conventional T cells into T reg cells and maintaining them (21)(22)(23). However, whether PD-1 expression by T reg cells during chronic infection is associated with the suppression of pathogen-specific T cell immune response remains unknown (24)(25)(26).…”
mentioning
confidence: 99%
“…T reg cells also upregulate PD-1 expression on their surfaces during chronic viral infection (20). PD-1:PD-L1 interaction has a critical role in promoting the conversion of conventional T cells into T reg cells and maintaining them (21)(22)(23). However, whether PD-1 expression by T reg cells during chronic infection is associated with the suppression of pathogen-specific T cell immune response remains unknown (24)(25)(26).…”
mentioning
confidence: 99%
“…Antigen-presenting cells, such as DCs, are essential for the expansion of Treg cells through costimulatory molecules B7 and ICOS and soluble factors, including TGF-␤ and prostaglandin E2 (PGE2). Recent studies have shown that Treg cells expand in response to Mycobacterium tuberculosis through mechanisms dependent on ManLAM, PGE2, PD-1, CISH, and PD-L1 (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36]46 The interaction of PD-L1 and 2 with PD-1, the members of CD28/B7 family, has a critical role in balancing the T-cell tolerance through inhibiting the activation of effector cells while promoting the generation and expansion of Tregs. 33,34 Pathogens such as Mycobacterium can hijack the immune system by activating the PD-L-PD-1 pathway and thus enhancing the Tregs and preventing the protective immune responses.…”
Section: Cd25mentioning
confidence: 99%